APPLYING TRANSCRIPT 1.23 IN IMPROVING THE STUDENTS’ WEAK FORMS AND CONNECTED SPEECH - Azman (LPPM STBA Pontianak, 2020)
This true experimental research is mainly aimed at investigating the effectiveness of using Computer-assisted Pronunciation Teaching (CAPT) application software Transcript 1.23 in teaching English pronunciation of weak forms and connected speech. The data used to measure the effectiveness of the application of CAPT software in the treatment is collected from participants’ oral performance in the form of voice records. The research involved the Government Islamic Senior High School 2 Pontianak. The pre-test and pos-test data from the participants is analysed and compared to measure the effect of the given treatment. The result of the research demonstrates a strong effect of the application of the software to improve the quality of the participants’ pronunciation of weak forms and connected speech. The effectiveness the application of the software is categorised as strong according to the criteria developed by Cohen.